Cardiovascular magnetic resonance (CMR) - An update and review - Myerson, S; Holloway, C; Francis, J; Neubauer, S (2011)
A review provides an overview of the existing cardiovascular magnetic resonance (CMR) techniques and their application to clinical problems and identify the main clinical areas of use. CMR needs to balance spatial with temporal resolution and to maximize the contrast between blood and myocardium. Tissue characterization of the myocardium itself is possible, with gadolinium contrast imaging and cardiac spectroscopy, and three-dimensional angiographic imaging with gadolinium is widely used. A high degree of interaction is required from the operator during the scanning to react to findings and to place imaging slices appropriately. The velocity of a tissue can be measured using the technique of phase velocity mapping which is applied to the flow of moving blood in CMR. Velocity can also be used to assess the severity of any stenosis across a valve or across a vessel.